2014
DOI: 10.1097/sla.0b013e318291da85
|View full text |Cite
|
Sign up to set email alerts
|

Burn Injury Enhances Bone Formation in Heterotopic Ossification Model

Abstract: Objective To demonstrate the pro-osteogenic effect of burn injury on heterotopic bone formation using a novel burn ossicle in vivo model. Background Heterotopic ossification (HO), or the abnormal formation of bone in soft tissue, is a troubling sequela of burn and trauma injuries. The exact mechanism by which burn injury influences bone formation is unknown. The aim of this study was to develop a mouse model to study the effect of burn injury on heterotopic bone formation. We hypothesized that burn injury wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
78
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 36 publications
4
78
1
1
Order By: Relevance
“…Recent evidence has shown that the development of HO following burn injury may be reduced in older subjects [37]. This is significant given that it has been documented for several years that the availability and functional activity of MSCs may be reduced with increasing age or passage [38].…”
Section: Mesoderm Mesenchymal Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence has shown that the development of HO following burn injury may be reduced in older subjects [37]. This is significant given that it has been documented for several years that the availability and functional activity of MSCs may be reduced with increasing age or passage [38].…”
Section: Mesoderm Mesenchymal Stem Cellsmentioning
confidence: 99%
“…Another novel strategy has been demonstrated in a burn-tenotomy rodent HO model [37] whereby hydrolysis of ATP at the burn site lead to reduced HO formation at a distant site. In addition to revealing a potential therapeutic strategy, this "remote ATP hydrolysis" method provides a further mechanistic insight into the role of phosphorylated SMAD proteins in the development of HO.…”
Section: Treatmentmentioning
confidence: 99%
“…This process occurs in two separate patient populations: those with severe trauma, including large surface-area burns, musculoskeletal injury, orthopedic operations, and even spinal cord injury; and those with a genetic disease known as fibrodysplasia ossificans progressiva (FOP) (1)(2)(3)(4). FOP is caused by a hyperactivating mutation in the type I bone morphogenetic protein (BMP) receptor ACVR1 (Activin type 1 receptor), and patients with FOP develop ectopic bone lesions in the absence of any substantial trauma.…”
mentioning
confidence: 99%
“…In the burn/tenotomy model, mice undergo Achilles' tendon transection with concomitant partial-thickness dorsal burn injury; HO forms in this model at the tendon transection site (2,3). To study genetic HO, two prominent models have evolved: (i) intramuscular HO through Ad.cre-inducible constitutively active ACVR1 (caACVR1: ACVR1 Q207D) with cardiotoxin injection (1), and (ii) congenital HO in conditional caACVR1 knockin mice [Nfatc1 (nuclear factor of activated T-cells, cytoplasmic 1)-cre/caACVR1 fl/wt ] (6).…”
mentioning
confidence: 99%
“…HO has been reported in at least 50% of patients who have incurred major burn injuries, suggesting that severity and size of injury significantly contribute to the production of HO. Additionally, the ectopic bone can be found distant to the actual burn injury 11. Recent military combat operations have heightened attention to war‐related wounds, 80% of which are caused by high‐energy explosive mechanisms.…”
Section: Trauma Statesmentioning
confidence: 99%